Charles Wesley and Lady Huntingdon: Erstwhile ‘Best of Friends’ - Maddox, Randy L. (Wesley and Methodist studies, 2026)
This article explores the intertwined lives of Charles Wesley and Selina (Shirley) Hastings, Countess of Huntingdon, highlighting how times of their closest cooperation coincided with periods of tension between Charles and his brother John. It draws on a number of resources only recently available (particularly materials that Charles Wesley recorded in shorthand) to provide a textured account of the warm relationship between these two ‘best of friends’ and the dynamics that led to its demise. In the process it adds insight into shifting currents within the eighteenth-century evangelical revival in England.